Microscopic visualization of heterogeneous nucleation process on smooth spherical particle: Method and results. (23rd February 2020) - Lv, Li; Zhang, Jun; Xu, Junchao
Highlights: A mixed surface is created to realize the prior condensation of water vapor. Heterogeneous nucleation process is firstly directly visualized. Only one embryo could be observed when vapor condenses on a smooth spherical single particle. The embryo drop occur on the interface of particles when vapor condenses on multiple particles. Heterogeneous nucleation behavior in high vacuum mode of ESEM is numerical analyzed. Abstract: Heterogeneous nucleation is a very fundamental step in vapor condensation. However, it is scarcely possible to directly visualize the nucleation process because it is very quick and complicated. In present work, a method is proposed to create a mixed surface, where the hydrophilic SiO2 particle is dispersed on the super-hydrophobic substrate for a direct visualization of the nucleation process. The time-resolved images are recorded by Environmental Scanning Electron Microscopy (ESEM) system. The results indicate that only one embryo drop forms at a random point of a single particle surface and subsequently grows up and finally wraps the single particle. For multiple particles, the embryo drop occurs on the junction of particles and continues to enlarge to finally wrap all the particles. The numerical analysis shows that the nucleation ability of SiO2 is qualitatively consistent with the theoretical prediction, and quantitatively, the experimental S cr is much smaller than the predicted results.